The Challenge of Child Rearing in the Pandemic Era: Accommodating a Fair Manner treatment Based on the Religion - Yeni Huriani (UIN Sunan Gunung Djati Bandung, 2021)
Women's responsibility for the family increased with the Work from Home (WFH) situation during the COVID-19 Pandemic. The entry of office and school into the family put excessive pressure on women, especially those who work. This study used the perspective of women's studies to find solutions to family problems during the COVID-19 Pandemic. This study took the setting of the urban situation in Cimahi City, West Java, Indonesia, in the early half of 2021, which is the time for the community to return to dealing with the lockdown conditions due to the emergence of the Delta Variant issue from COVID-19. This study uses a sociological analysis of 15 families through direct observation and interviews. This study found that men play a dual role between being a worker and being a nanny at home to help their wives. The presence of fathers who work at home makes them closer to their children, and they feel happy to be able to work at home while educating their children. Similarly, the family structure works well, and there is no overlap between the roles of husband and wife. The respondents felt it was a religious obligation, namely to help each other in goodness. This research can provide a solution for family resilience in the face of a social environment that changes attitudes and ways of working in the family.